Risk factors for death in patients with sepsis in an intensive care unit - Prado, Patricia Rezende do (2018)
Objective: to determine the main risk factors for death in patients with sepsis in an intensive care unit. Methods: it is a retrospective cohort study, wich included 126 patient chorts lhat had clinical and clinical and laboratory diagnosis of sepsis were considered eligible. The conditional probability of death was calculated through the Kaplan-Meier method and the risk of death was estimated by the hazard ratio, using a Cox regression model with p<0.050. Results: a total of 124 patients were included in the study. The main focus of infection was the respiratory system. Regarding the outcome, 40.3% patients with sepsis, 73.9% with severe sepsis and 69.2% with septic shock died. Patients with abdominal sepsis and using vasopressors were at higher risk of death. Conclusion: septic patients with abdominal source of infection and using vasopressor agents had a higher risk of dying, while patients who were tracheostomized had a better chance of living.